2021
DOI: 10.1111/grs.12318
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer application increases nitrate nitrogen concentration in Urochloa brizantha cv. MG5 as annual summer grass in temperate zone

Abstract: Webster syn. Brachiaria brizantha (A. Rich.) Stapf) is a grass grown widely in Brazil (Flores et al., 2008). Experimental lines and cultivars have been introduced to tropical Asia and Pacific region (Schultze-Kraft, 1992, i.e., Thailand;Hare et al., 2005).Palisadegrass has also been introduced not only in the tropics, but also in subtropical areas such as Florida in the United States (Inyang et al., 2010;Vendramini et al., 2012) and warm temperate zones such as southwestern Japan (Nitthaisong et al., 2017).We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The lower weed mass in the FSR and HSR than in the BR at 12 weeks did not result in greater brachiariagrass HA, likely due to competition with sunn hemp and sudangrass in the initial phases of the experimental period. Kaneko, Nakamura, Yamada, et al (2021) reported that basal fertilizer has no effect on the early growth of palisadegrass but promotes weed growth. The basal fertilization used in this study may have enhanced early weed growth, especially in the BR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The lower weed mass in the FSR and HSR than in the BR at 12 weeks did not result in greater brachiariagrass HA, likely due to competition with sunn hemp and sudangrass in the initial phases of the experimental period. Kaneko, Nakamura, Yamada, et al (2021) reported that basal fertilizer has no effect on the early growth of palisadegrass but promotes weed growth. The basal fertilization used in this study may have enhanced early weed growth, especially in the BR treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MG5, with an IRS of 120 cm, (which we refer to as wide-row seeding cultivation), could produce a suitable forage yield (over 1 kg dry matter m -2 in Field Experiments 3, 4, and 5), in association with weed control by intertillage using a 10 kW-level tractor with a rotary tiller. Kaneko et al (2012) and Uesugi et al (2015) conducted palisade grass cultivation experiments with BSC at a seeding density of 4 g m -2 , while Hanagasaki et al (2008) and Nitthaisong et al (2017) used a seeding density of 3 g m -2 . Kaneko et al (2018) also conducted BSC of palisade grass at seeding densities of 2 and 4 g m -2 , and suggested that the lower seeding density (2 g m -2 ) tended to reduce the forage yield in the first harvest, and it was difficult to control weeds using BSC with a seeding density of less than 4 g m -2 .…”
Section: Field Experiments 4 (2013): Comparison Between Row Seeding C...mentioning
confidence: 99%
“…Kaneko et al (2012) and Uesugi et al (2015) conducted palisade grass cultivation experiments with BSC at a seeding density of 4 g m -2 , while Hanagasaki et al (2008) and Nitthaisong et al (2017) used a seeding density of 3 g m -2 . Kaneko et al (2018) also conducted BSC of palisade grass at seeding densities of 2 and 4 g m -2 , and suggested that the lower seeding density (2 g m -2 ) tended to reduce the forage yield in the first harvest, and it was difficult to control weeds using BSC with a seeding density of less than 4 g m -2 . We used a seeding density of 4 g m -2 for BSC in our Field Experiment 4, and obtained very high W/CRs, suggesting that palisade grass sown using BSC at this seeding density is a weak competitor in comparison with weeds, especially during the initial growth stage.…”
Section: Field Experiments 4 (2013): Comparison Between Row Seeding C...mentioning
confidence: 99%
See 2 more Smart Citations